ANALISA PRESSURE DROP PADA INSTALASI PIPA ALAT UJI RUGI-RUGI ALIRAN MENGUNAKAN CFD FLUENT 6.0 - Sepfitrah -; Yose Rizal (Universitas Pasir Pengaraian, 2013)
This study aims to determine the magnitude of the effect of component geometry pipeline and the pipe roughness on the performance of the pump and the pressure drop caused, then perform simulations to determine the fluid flow losses in pipe flow by using computational fluid dynamics program FLUENT 6.0 program package.Methods and objects used in this study is a series of piping by using various types of piping components. Installation tool is a Loss-Loss Test Equipment Flow Laboratory located in Pekanbaru STTP.From the results of tests performed in an actual magnitude of the resulting gas flow without doing the loading, when it is connected to the pipe line 1 maximum of 29 l / min at 2812 rpm rotation pump, and when connected to the pipe line 2 flow rate 35 l / min with the rotary pump 2849 rpm.